Look Back Before Leaping Forward: Four Decades of Domestic-Energy Inquiry - Hazas, Mike; Friday, Adrian; Scott, James (IEEE Pervasive Computing, 2011)
Reducing domestic energy consumption has a long, varied history, embracing pervasive computing, technology, sociology, and economics. The authors provide an overview and key references to help readers explore this rich background more deeply and broadly.